2009
DOI: 10.1021/nn800551s
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Killing of Cancer Cells in Vivo and in Vitro with EGF-Directed Carbon Nanotube-Based Drug Delivery

Abstract: Carbon nanotube-based drug delivery holds great promise for cancer therapy. Herein we report the first targeted, in vivo killing of cancer cells using a drug-single wall carbon nanotube (SWNT) bioconjugate, and demonstrate efficacy superior to non-targeted bioconjugates. First line anti-cancer agent cisplatin and epidermal growth factor (EGF) were attached to SWNTs to specifically target squamous cancer, and the non-targeted control was SWNT-cisplatin without EGF. Initialin vitro imaging studies with head and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
534
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 813 publications
(542 citation statements)
references
References 59 publications
6
534
0
2
Order By: Relevance
“…A particularly interesting is their use in the field of biomedicine: in biosensors [6,7], medical diagnostics [8,9], transplantology [10,11], tissue engineering [12] or in pharmacology -including the field of targeted therapies [13][14][15][16].…”
Section: Methods Of Dispersing Carbon Nanotubes -The Search For Optimmentioning
confidence: 99%
“…A particularly interesting is their use in the field of biomedicine: in biosensors [6,7], medical diagnostics [8,9], transplantology [10,11], tissue engineering [12] or in pharmacology -including the field of targeted therapies [13][14][15][16].…”
Section: Methods Of Dispersing Carbon Nanotubes -The Search For Optimmentioning
confidence: 99%
“…poor solubility) and potential as the fullerene counterparts, such as drug design, drug delivery, tumor therapy, tissue engineering, DNA recognition, and biosensor design. [58][59][60][61][62] Besides, CNT is often used as a representative hydrophobic nanoparticle to study the role hydrophobic interaction plays in the protein-nanoparticle interaction, and the impact on the protein structure and function. Ruhong Zhou and co-workers took WW domains (i.e.…”
Section: Carbon Nanotube Cntmentioning
confidence: 99%
“…Thus, cisplatin and EGF were attached to single-wall carbon nanotubes (SWNTs) to target squamous cancer cells HNSCC which overexpress EGFR. Through Qdot luminescence and confocal microscopy, it was shown that SWNT-Qdot-EGF bioconjugates was rapidly internalized into the cancer cells, and HNSCC cells were selectively killed in vitro, while tumor growth was regressed in vivo [31]. A current cancer treatment that targets EGFR is the monoclonal antibody Cetuximab, which targets the extracellular domain of EGFR and small-molecule inhibitors of tyrosine kinase activity [66].…”
Section: Human Epidermal Receptormentioning
confidence: 99%